STRATEGI PEMASARAN WINGMAN DENIM DI BANDAR LAMPUNG DENGAN MATRIKS BOSTON CONSULTING GROUP (BCG) - Aswin -; Reva Devara (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2017)
Wingman Denim is a business in jeans industry which the quality of the jeans uses premuiummaterials that are comparable with Levi’s, Lee Cooper, Wrangler, and Pot Meets Pop. The Company isalso very concerned about the factor that affect the number of purchases each month based onmarketing strategics that have been used. The high level of competition among brands of jeans inBandar Lampung offering jeans with premium quality, so it sparks the competitions for this business onBandar Lampung.The problem in this research was the promotion program run still didn’t know about WingmanDenim in Bandar Lampung, Wingman Denim distribution channels in Bandar Lampung was also stilllimited and Wingman Denim Only had one store so that consumers who live for fom the range of shopwould get difficulty to obtain the product from Wingman Denim. The study objective was to determinethe accuracy of the marketing strategy on Wingman Denim jeans store to marketing their product.The analysis toot used was BCG matrix. The results study with BCG matrix indicate that marketgrowth for Wingman Denim through July 2015 to December 2015 amounted to 7,63 %. This suggeststhat the market growth rate Wingman Denim in Bandar Lampung was still low due to their the amount ofgrowth in the market was still below 10 %. Based on market share analysis, the value of 0,39 times themarket share in the first quarter and 0,41 time in the second quarter, it shows that the market shareWingman Denim in Bandar Lampung is still low because, it is still less than 1.